Institutional Investors, Political Connections and Analyst Following in Malaysia - How, J.; Verhoeven, P.; Abdul Wahab, Effiezal Aswadi (Elsevier BV * North-Holland, 2014)
We examine the association between institutional ownership, political connections, and analyst following in Malaysia from 1999 to 2009. Based on 940 firm-year observations, we document a positive relation between institutional ownership, particularly by Employees Provident Fund (EPF), and analyst following, thus supporting the governance role that institutional investors play in promoting corporate transparency. However, there is no evidence that political connections matter to analyst following. The monitoring role of institutional investors, including EPF, does not appear to be any different between politically connected and non-connected firms.